2014
DOI: 10.1097/sle.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Choice of Intervention Influences Outcome in Acute Cholecystitis

Abstract: A high complication rate seen with radiology placed percutaneous cholecystostomy tubes prompted our center to reevaluate the treatment algorithm used to treat patients with complex acute cholecystitis. Although laparoscopic cholecystectomy is considered to be the gold standard in the treatment of acute cholecystitis, if laparoscopic cholecystectomy is not felt to be safe due to gallbladder wall thickening or symptoms of >72 hours' duration, we now encourage the use of intravenous antibiotics to "cool" patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Patient satisfaction is reduced with these delayed approaches (75.34 AE 12.85 versus 92.66 AE 6.8, P 0.0001), whereas number of readmissions and total mean hospital days (5.7 AE 2.32 versus 2.4 AE 1.1 d, P 0.0001) are increased compared with those with early operative intervention [20]. Cholecystostomy tubes are also prone to blockage, dislodgement, and can cause injury on placement with overall complication rates as high as 47.8% when placed in radiology and 33.3% when placed operatively [19]. However, these studies reports outcomes on all patients presenting with acute cholecystitis and the conclusion that early intervention is optimal may not translate to special high-risk subpopulations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Patient satisfaction is reduced with these delayed approaches (75.34 AE 12.85 versus 92.66 AE 6.8, P 0.0001), whereas number of readmissions and total mean hospital days (5.7 AE 2.32 versus 2.4 AE 1.1 d, P 0.0001) are increased compared with those with early operative intervention [20]. Cholecystostomy tubes are also prone to blockage, dislodgement, and can cause injury on placement with overall complication rates as high as 47.8% when placed in radiology and 33.3% when placed operatively [19]. However, these studies reports outcomes on all patients presenting with acute cholecystitis and the conclusion that early intervention is optimal may not translate to special high-risk subpopulations.…”
Section: Discussionmentioning
confidence: 92%
“…Although laparoscopic cholecystectomy is the gold standard of care for acute cholecystitis, alternative acceptable treatment includes intravenous antibiotics followed by an interval laparoscopic cholecystectomy. For complicated acute cholecystitis or persistent symptoms, a percutaneous cholecystostomy tube placed under radiographic guidance is another option in addition to the mentioned antibiotics and interval cholecystectomy [1,19]. Patient satisfaction is reduced with these delayed approaches (75.34 AE 12.85 versus 92.66 AE 6.8, P 0.0001), whereas number of readmissions and total mean hospital days (5.7 AE 2.32 versus 2.4 AE 1.1 d, P 0.0001) are increased compared with those with early operative intervention [20].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 89 full‐text articles were assessed for eligibility, and 26 articles were included in the study. Details of relevant excluded studies are shown in Table S1 (supporting information). Of the 26 included articles, 24 were eventually used in the meta‐analysis, because four described the same two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic cholecystectomy (LC) is a frequently performed operation and is the gold standard for the treatment of many biliary disease processes such as cholelithiasis and cholecystitis 5 6. Well-recognized complications of laparoscopic cholecystectomy include bile leak, common bile duct injury, hemorrhage, retained gallstone, and wound infections 7–9.…”
Section: Introductionmentioning
confidence: 99%